2014
DOI: 10.1016/j.sjbs.2013.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Computational identification of miRNA and targets from expressed sequence tags of coffee (Coffea arabica)

Abstract: MicroRNAs (miRNAs) are the group of ∼22 nucleotides long noncoding small endogenous and evolutionary conserved post-transcriptional regulatory RNAs, which show an enormous role in various biological and metabolic processes in both animals and plants. To date not a single miRNA has been identified in coffee (Coffea arabica), which is an economically important plant of Rubiaceae family. In this study a well-developed, powerful and comparative computational approach, EST-based homology search is applied to find p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 52 publications
0
33
0
Order By: Relevance
“…This indicates that miRNAs widely exist in the genus Coffea and further demonstrates that many miRNAs are highly evolutionary conserved among species in the plant kingdom. Similarly, only one miRNA was reported by Akter et al, (2014) in Coffea arabica, 58 miRNA sequences belonging to 33 miRNA families from Coffea canephora and Coffea arabica were reported by Loss-Morais et al (2014), and 18 miRNAs belonging to 14 miRNA families from Coffea arabica were reported by Rebijith et al, (2013). The miRNA families miR-160, -162, -164, -165, -171, -397, -408, -479, and -2111 were reported for only mature miRNA sequences by Loss-Morais et al (2014) and were also found in this study with pre-miRNA sequences and secondary self-folded stem-loop structures.…”
Section: Coffeamentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that miRNAs widely exist in the genus Coffea and further demonstrates that many miRNAs are highly evolutionary conserved among species in the plant kingdom. Similarly, only one miRNA was reported by Akter et al, (2014) in Coffea arabica, 58 miRNA sequences belonging to 33 miRNA families from Coffea canephora and Coffea arabica were reported by Loss-Morais et al (2014), and 18 miRNAs belonging to 14 miRNA families from Coffea arabica were reported by Rebijith et al, (2013). The miRNA families miR-160, -162, -164, -165, -171, -397, -408, -479, and -2111 were reported for only mature miRNA sequences by Loss-Morais et al (2014) and were also found in this study with pre-miRNA sequences and secondary self-folded stem-loop structures.…”
Section: Coffeamentioning
confidence: 99%
“…It also has medicinal properties because of secondary metabolites like polyphenols, caffeine, theobromine, and chlorogenic acids (Ferrazzano, 2009). To our knowledge, although progress has been made on the genus Coffea, there is little knowledge about miRNAs in Coffea (Rebijith et al, 2013;Akter et al, 2014;Loss-Morais et al, 2014). In this study, we employed a well-defined comparative genomebased homolog search to identify Coffea miRNAs.…”
mentioning
confidence: 99%
“…Some in silico efforts have been performed to describe miRNAs in C. arabica [1,40], identifying 15 and 1 miRNA families, respectively. In addition to that, recently, deepsequencing libraries have been generated using both genomic [11] and transcriptomic [29] data of C. canephora.…”
Section: Characteristics Of Potential Coffee Mirnas Identifiedmentioning
confidence: 99%
“…In addition, ESTs can be used as an alternative approach for the discovery of pre-miRNAs, particularly in species lacking a draft genome sequence. This approach has been used to identify many premiRNAs in various crops, including miRNAs from maize wheat (Han et al, 2009), sugarcane (Zanca et al, 2010), coffee (Akter et al, 2013); jatropha (Vishwakarma and Jadeja, 2013), and tomato (Din and Barozai, 2014).…”
Section: Introductionmentioning
confidence: 99%